A new approach to automated assessment of fractionation of endocardial electrograms during atrial fibrillation - Kremen, V; Lhotská, L; Macas, M; Cihák, R; Vancura, V; Kautzner, J; Wichterle, D (Physiological measurement, 2008)
Complex fractionated atrial electrograms (CFAEs) may represent the electrophysiological substrate for atrial fibrillation (AF). Progress in signal processing algorithms to identify sites of CFAEs is crucial for the development of AF ablation strategies. A novel algorithm for automated description of fractionation of atrial electrograms (A-EGMs) based on the wavelet transform has been proposed. The algorithm was developed and validated using a representative set of 1.5 s A-EGM (n = 113) ranked by three experts into four categories: 1-organized atrial activity; 2-mild; 3-intermediate; 4-high degree of fractionation. A tight relationship between a fractionation index and expert classification of A-EGMs (Spearman correlation rho = 0.87) was documented with a sensitivity of 82% and specificity of 90% for the identification of highly fractionated A-EGMs. This operator-independent description of A-EGM complexity may be easily incorporated into mapping systems to facilitate CFAE identification and to guide AF substrate ablation.
Keywords: senioři; elektrokardiografie; algoritmy; Algorithms; Signal Processing, Computer-Assisted; katetrizační ablace; Middle Aged; mužské pohlaví; Automation; Catheter Ablation; Electrocardiography; ženské pohlaví; Humans; interpretace statistických dat; Data Interpretation, Statistical; fibrilace síní; pilotní projekty; lidé středního věku; Pilot Projects; automatizace; Female; Aged; počítačové zpracování signálu; Atrial Fibrillation; lidé; Male